Programa didáctico “Aprendo a razonar jugando” ´para el desarrollo de las habilidades matemáticas en los niños/as de 5 años del nivel inicial de la I.E N°089 del sector Nueva Rioja - López Amaringo, Shirley (2012)
We understand education as integral formation of the person. We believe that the work of teachers is to prepare students in class today to live and work in tomorrow's world, in an increasingly complex society that requires people who can solve problems and adapt to different situations (Burrill, 1998; Chamoso and Rawson, 2003). So far it has taught students to make, not to think. But mathematics is not merely a collection of facts and skills but, above all, a way of thinking (Kehle, 1999). Many studies recommend that students should learn to value mathematics, . feel secure in their ability to do mathematics, reaching solve math problems, learn to communicate through mathematics and learn to reason mathematically. The art of teaching has little to do with trade in knowledge, its primary purpose must be to promote the art of learning (von Glasersfeld, 1995). However, one can not forget the fact that it is the area of mathematics in which lower yields are obtained (INCE, 1997) and is perceived as the most difficult (eg Alcalá, 1997), although both are considerad important and highly predictive of individual abilities (Guerrero Ojeda, 1989). The truth is disliked by many people who see it as something alien. So the teacher who leaves his role of authority and provides information to become somebody who facilitates learning should encourage students and nurture their curiosity, encourage interaction between them, diversify the means used (materials manipulatives) and way of organizing work (small groups, individual performances, presentation to the entire class.). The goal is for students to have confidence in themselves, develop their mathematical ability and value this science. The potential is that games are engaging activities and easily accepted by students that are varied, recognize them as elements of reality and.allow them to develop their competitiva spirit. A playful atmosphere contributes to arouse the curiosity of students and help them to enjoy the joy of discovery and the pleasure of knowledge (Guzmán, 1996). Any game situation to arise in the classroom will promote social development of students as stimulate dealing with others, peer collaboration and teamwork, in addition, require effort, rigor, attention and memory, stimulate the imagination, . foster creativity and teach critica! thinking (Chamoso and Duran, 2003). The most significant of these potentials is that the games are generating lasting learning. The skills acquired in enjoyable learning conditions normally retained for periods of time than those acquired by taxation or in adversa conditions and not forgotten after overcoming short-term goals as examinations (Gallagher, 1980). The research focused his interest in a group of children 5 years old of School of initial N ° 089, the city of Rioja to insert through an educational program, recreational activities in the development of learning sessions to develop math skills. The description and interpretation of variables turns a theoretical framework presentad in the first arder the current scientific approach that dominates the design of logical and mathematical child's play as second-order technical tool that facilitates teaching and learning process effective the in the area of mathematical logic. Our objective was to describe the efficiency of the educational program Learning to Argue Playing for effective stimulation and achieve the development of mathematical skills in a group of children from 5 years of School No. 089 on the initial level of Rioja city taking a group of 20 students to implement the experimental process.